Science Technology Engineering and Math (STEM) Based Learning Model in Biology Learning at Islamic Senior High School - Sudarmaji, Asahy Syadza (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
The purpose of this study was to analyze the percentage level of STEM occurrence in biology textbooks. The population used in this study was two biology teachers. The sample was taken using a purposive sampling technique. This data collection instrument is a human instrument. The approach uses STEM, and the type of research is descriptive qualitative. The data were analyzed descriptively; the data sources used in this study came from the curriculum, KI/KD lesson plans, and biology textbooks. Data analysis techniques using STEM indicators. The results showed the percentage of STEM occurrence rate in biology textbooks class X semester II by validator I had 17,5% Science components, 5,7% Technology, 25,6% Engineering, and 5,0% Mathematics; validator II had 17,5% Science components, 50,5% Technology, 26,0% Engineering, and 5,8% Mathematics; validator III had 17,5% Science components, 51,7% Technology, 25,6% Engineering, and 5,0% Mathematics. The average occurrence of STEM components is science as much as 17,5%, Technology as much as 51,3%, Engineering as much as 25,7%, and Mathematics as much as 5,2%. The assessment of the validator received a very suitable category with an assessment of 99,8% in the biology textbook at MAN 1 Medan class X semester II.